Unveiling the distribution of free and bound phenolic acids, flavonoids, anthocyanins, and proanthocyanidins in pigmented and non-pigmented rice genotypes - Avinash, Gosangi; Sharma, Neerja; Prasad, Kalluri Rajendra; Kaur, Rupinder; Singh, Gurjeet; Pagidipala, Nagaraju; Thulasinathan, Thiyagarajan (Frontiers in Plant Science, 2024)
ABSTRACT The total phenolic content, phenolic acid profile, anthocyanins, proanthocyanidins, flavonoids, and antioxidant capacity of the whole-grain and bran portion of sixteen distinct rice genotypes that correspond to three distinct pericarp bran colours—black, red, and non-pigmented (NP)—were examined. Ten free and bound phenolic acids, as well as two flavonoids, were analyzed using HPLC-PDA. The flavonoids included kaempferol and catechin hydrate, and the free phenolic acids including gallic acid, 2,5-dihydroxybenzoic acid, vanillic acid, syringic acid, p-coumaric acid, chlorogenic acid, trans-cinnamic acid, trans-ferulic acid, p-coumaric acid, and sinapic acid. Trans-ferulic acid (207.39 mg/kg), p-hydroxybenzoic acid (94.36 mg/kg), and p-coumaric acid (59.75 mg/kg) were the principal bound phenolic acids in pigmented rice genotypes, whereas in NP genotypes they were trans-ferulic acid (95.61 mg/kg) and p-hydroxybenzoic acid (58.32 mg/kg). The main free phenolic acid was syringic acid (120.43 mg/kg) in all genotypes. 2,5-dihydroxybenzoic acid was also detected in NP genotypes, mainly in the bound form (4.88 mg/kg). NP genotypes Basmati 386 and Punjab Basmati 7 also displayed high content of bran flavonoids (1001 and 1028 mg CE/100 g). The bound form of phenolics had significant DPPH and ABTS + activity. This study found wide diversity in the phenolic acid profile, total phenolic constituents, and antioxidant activity in the bran and whole grain of pigmented and NP rice. The individual phenolic acids in free and bound forms in different fractions of the grain were found to exert their antioxidant activity differently. The results obtained will provide new opportunities to improve the nutritional quality of rice with enhanced levels of phytochemicals in the ongoing breeding programs. Black rice bran contains a high level of phytochemicals and thus has a potent pharmaceutical role. This information would enhance the use of whole-grain and bran of pigmented rice in food product development by food technologists. Further studies may be focused on clinal trials with respect to cancer and diabetes.